PENYALURAN KREDIT BANK DITINJAU DARI JUMLAH DANA PIHAK KETIGA DAN TINGKAT NON PERFORMING LOANS - Imam Mukhlis (Jurnal Keuangan dan Perbankan, 2011)
This research aimed to analyze the effect of money deposit on the bank and non performing loans on creditallocation from Bank Rakyat Indonesia in 2000-2009. The method of analyze was dynamic regression modelby Error Correction Model (ECM) approach version Domowitz and Elbadawi. Our empirical results showedthat only non performing loan on the short term had a significant effect to credit allocation from Bank RakyatIndonesia on the short term and long term. The variable money deposit of the bank did not have a significanteffect on credit allocation from Bank Rakyat Indonesia both on short term and long term period.